A comparative study of attitudes and motivation of Croatian learners of English and German - Mihaljević Djigunović, Jelena; Bagarić, Vesna (2007)
In this comparative longitudinal trend study the authors compare attitudes and motivation of Croatian learners of English and German. Comparisons are made not only with respect to the FL but also to two age points of the learners’ language and affective development: end of primary education (age 14) and end of secondary education (age 18). In the study both the quantitative and qualitative research paradigms were employed. Data was gathered by means of a questionnaire consisting of three parts, including both structured and open-ended items. Conclusions are made on the basis of combined quantitative and qualitative results. Implications for further research are offered as well.
Projekt MZOS
ENG